Optimization of a short-range surface-to-air artillery-missile system design process using the hybridized triangular IT2FS-DEMATEL-MABAC approach - Petrović, Ivan; Petrović, Milan (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The possibility of optimizing a short-range surface to air artillery-missile system (short-range SAAM) design process by applying hybridized multi-criteria decision-making (integration of DEMATEL and MABAC methods) approach in the triangular interval type 2 fuzzy environments is shown in the paper. By analyzing the content of the literature, the selection of the tactical-technical requirements and sub-requirements were determined. Furthermore, in the paper the weights of requirements and sub-requirements are determined. After that, a multi-criteria decision-making (MCDM) model was created for the evaluation of different initial projects of designing the short-range SAAM, which was also tested in this paper.Methods: The proposed approach that combine DEMATEL and MABAC methods have been modified by triangular interval type 2 fuzzy sets (IT2FS). The triangular IT2F-DEMATEL method was applied to determine the requirements’ and sub-requirements’ weights, and the triangular IT2FS -MABAC method was applied to evaluate the alternatives – initial project designs of the short-range SAAM.Results: Integrating multiple the triangular IT2FS-MCDM approach into a unique model that can be applied in the process of defining the optimal initial design project of the short-range SAAM.Conclusion: The paper contributes to military science in making decisions related to the design of the short-range SAAM.
Keywords: DEMATEL, MABAC, Triangular Interval Type 2 Fuzzy Sets, Short-Range Surface-to-Air Artillery-Missile System.